ISOLATION OF HERPES SIMPLEX VIRUS (HSV) FROM VESICULAR LESIONS (Vietnam Journal of Community Medicine, 2026)
Objective: To isolate HSV from clinical samples of vesicular lesions on Vero cells.Methods: A cross-sectional study was conducted on vesicular lesions suspected by HSV.Results: Twenty strains of HSV (HSV-1 and HSV-2) were isolated on African green monkey kidney cells (Vero) from 37 clinical samples of facial and genital vesicular lesions suspected by HSV (54,1%). Among these, 90% of the strains were isolated from facial herpes. The positivity rate in the group that had not used specific antiviral drugs before sample collection was higher than that had used, although this difference was not statistically significant. The positivity rates also showed no significant difference between males and females. The study obtained 12 strains from patients who had not used specific any antiviral drugs (naiive), which could be used for identification of genetic polymorphisms of HSV strains circulating in Vietnam.Conclusion: In this study, a relatively high positivity rate (54.1%) was observed when isolating HSV on Vero cells from vesicular skin lesions. Isolated virus strains can be submitted for phenotypic testing of determination of susceptibility of HSV to antiviral drugs and evaluation of the efficacy of new antiviral drugs.
Keywords: HSV, isolation, vesicle, Vero, ACV